A novel addition to the Pezizellaceae (Rhytismatales, Ascomycota) - Karunarathna, Anuruddha; Działak, Paweł; Jayawardena, Ruvishika S.; Karunarathna, Samantha Chandranath; Kuo, Chang-Hsin; Suwannarach, Nakarin; Tibpromma, Saowaluck; Lumyong, Saisamorn (Phytotaxa, 2021)
In previous studies Apiculospora was introduced in Leotiomycetes genera incertae sedis. With our phylogenetic analyses based on large subunit rDNA (LSU) and internal transcribed spacer (ITS1, 5.8S, ITS2), we transfer Apiculospora to Pezizellaceae (Rhytismatales). We introduce Apiculospora penniseti from Pennisetum purpureum. Apiculospora penniseti differs from the closely related A. spartii by the presence of clear apiculi at both apices of the smooth-walled ascospores. Apiculospora penniseti is phylogenetically distinct from A. spartii with moderate support and high BYPP support (69 RAxML/0.97 BYPP). Herein, we discuss the taxonomy and phylogeny of A. penniseti.